Long noncoding RNA TUG1 promotes proliferation and inhibits apoptosis in multiple myeloma by inhibiting miR-29b-3p. Issue 3 (22nd March 2019) - Liu, Dahai; Wang, Jianfeng; Liu, Meihan
Abstract : Background : Long non-coding RNA taurine up-regulated gene 1 (TUG1) was reportedly involved in initiation and development of several cancers. However, its function and molecular mechanisms in multiple myeloma (MM) are still unclear. The present study aimed to determine the expression status, biological function, and potential mechanisms of TUG1 in the progression of MM. Materials and methods: The expression levels of TUG1 were examined in MM samples and cell lines by real-time quantitative PCR. The effects of TUG1 on MM cells proliferation and apoptosis were assessed using Cell Counting Kit-8 assay and flow cytometry respectively. MiRNAs-targeted sites in TUG1 were screened by Starbase2.0 and were identified by RNA immunoprecipitation assay combined with luciferase reporter assay. Results : The expression levels of TUG1 were markedly increased in MM samples and cell lines. Knockdown of TUG1 significantly suppressed the proliferation, induced cell cycle arrest at G1/G0 phase, and promoted apoptosis of MM cells. In exploring the regulatory mechanism, miR-29b-3p was confirmed to be a direct target of TUG1, and repression of miR-29b-3p could partially rescue the effect TUG1 knockdown on MM cell proliferation, cycle, and apoptosis. In addition, TUG1 positively modulated histone deacetylases 4 (HDAC4, a target of miR-29b-3p) expression through sponging of miR-29b-3p in MM cells. Conclusion : These findings suggested that TUG1 exerted an oncogenic role in MM by acting as a competing endogenous RNA of miR-29b-3p, and implied the potential application of TUG1 in treatment for MM.